The dental service and dental health of Northern Newfoundland and Labrador: a twenty year study - Messer, James G. (1990)
Dental Health Care has been provided by the Grenfell Association for the people of Northern Newfoundland and Labrador since the late 1800’s. The capability to provide dental care has been influenced by many factors including a small population living in isolated communities over an enormous geographical area with adverse climatic conditions and long lines of communication. Transportation alone presented a formidable challenge. Based on his early experience with the Association between 1964-69, the author realised, on his return to Canada in 1976 that there was need to identify major problems, adapt existing facilities and change established philosophies, as well as to introduce new systems and methods to improve dental health-care delivery. The main areas of concern were the high prevalence of dental disease, the lack of adequate manpower, appalling working conditions and lack of overall policies. Initially, one of the major tasks was to establish basic equipment at each clinic. Small portable light-weight dental units were designed and constructed by the author, for each dentist with a travelling commitment, these units being readily connected to on-site compressors. Thereafter, a longterm policy of equipment upgrading and replacement was pursued to enable dental staff to undertake a complete range of clinical duties. Later, when new Health Centres and Nursing Stations were established, the author had the opportunity to become involved in their design and layout. The method of dental service financing also contributed to many of the problems. Thus the existing monetary arrangements had to be studied which, in turn, required an understanding of the sources of funding. Hence, following analysis of financial data collected after only the first few months of 1976, it became clear that several issues required urgent action and, as monetary considerations appeared to be the crux or the problem, the author decided to introduce a standard billing system which was applied throughout the region. This was primarily ...